2017
DOI: 10.1016/j.juro.2017.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Cohort of Prenatally Diagnosed and Early Enrolled Patients with Congenital Solitary Functioning Kidney

Abstract: In an evaluation of a large cohort of patients enrolled early with congenital solitary functioning kidney with a prenatal diagnosis, excluding those with neonatal onset of renal damage, the prevalence of renal damage was 3.9%. Among congenital anomalies of the kidney and urinary tract, congenital solitary functioning kidney represented the major risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…Since a decrease in kidney function is expected later in the course of hyperfiltration injury, serum creatinine measurement can be performed less frequently than screening for hypertension and albuminuria. Indeed, cSFK cohorts published to date showed that an isolated decrease in estimated GFR (eGFR) occurred in only 0.3–8% of their population and may especially occur during puberty [6] , [7] , [52] , [53] , [54] . Therefore, it seems reasonable to monitor eGFR once every 5 yr until the onset of puberty and every 2 yr thereafter.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Since a decrease in kidney function is expected later in the course of hyperfiltration injury, serum creatinine measurement can be performed less frequently than screening for hypertension and albuminuria. Indeed, cSFK cohorts published to date showed that an isolated decrease in estimated GFR (eGFR) occurred in only 0.3–8% of their population and may especially occur during puberty [6] , [7] , [52] , [53] , [54] . Therefore, it seems reasonable to monitor eGFR once every 5 yr until the onset of puberty and every 2 yr thereafter.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Living with a cSFK predisposes to hypertension, proteinuria, and kidney function loss [4] , [5] , [6] . The magnitude of the risk of living with a cSFK is still a topic of debate, with kidney injury rates ranging from 6% to 60% at age 15 and limited studies in adulthood [6] , [7] . In addition, large differences exist in the management of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies the prognosis for children with a congenital SFK is suggested to be more favorable. Indeed, in a recent retrospective study of ∼300 children prenatally diagnosed with a congenital SFK, only 3.9% had signs of kidney injury by a median age of 7 years ( Marzuillo et al, 2017 ). Similarly, La Scola et al (2016) observed that in a cohort of 146 children with a congenital SFK, only 5% of patients had hypertension at a mean age of 12 years and only 4% presented with proteinuria at a mean age of 6 years.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Over half of pregnancies involving severe CAKUTs have adverse birth outcomes, such as stillbirth or even spontaneous abortion [6]. Among live births, CAKUTs are closely associated with impaired renal function, particularly chronic kidney and kidney-related diseases in young adults [710]. For example, approximately 39.8% of end-stage renal disease cases in patients younger than 20 years old in Japan are owing to CAKUTs [9].…”
Section: Introductionmentioning
confidence: 99%